2014
DOI: 10.3991/ijet.v9i8.3805
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Innovation within Facebook: A Case Study in Tertiary Education in Palestine

Abstract: Abstract-The proliferation of Facebook use among students and teachers has created a new learning culture by providing innovative ways for teachers to enable learners to engage actively in different learning activities. This paper investigates the potential use of the Facebook social network site to support faculty in implementing a social constructivist approach to facilitate student-centred learning. To alleviate problems arising from poor student engagement in large classes, 240 students from An-Najah Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 13 publications
0
20
0
3
Order By: Relevance
“…In a similar vein, several authors reported that the use of Facebook as an LMS had the potential to engage students even in out‐of‐class discussion with instructors and to increase student motivation, peer learning and feedback (Albayrak & Yildirim, ; Bariş & Tosun, ; Geyer, ; Karal et al, ; Miron & Ravid, ; Musa et al, ; O'Bannon, Beard, & Britt, ; O'Bannon, Britt, & Beard, ; Omar, Embi, & Yunus, ; Öztürk, ; Rachtam, Kaewkitipong, & Firpo, ; Rubrico & Hashim, ; Shih, ; Shraim, ; Souleles, ; Staines & Lauchs, ; Stankov, Glavinić, & Krpan, ; Varol, ; Vincent & Weber, ; Wang, Leng, & Lee, ).…”
Section: Formal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 98%
See 1 more Smart Citation
“…In a similar vein, several authors reported that the use of Facebook as an LMS had the potential to engage students even in out‐of‐class discussion with instructors and to increase student motivation, peer learning and feedback (Albayrak & Yildirim, ; Bariş & Tosun, ; Geyer, ; Karal et al, ; Miron & Ravid, ; Musa et al, ; O'Bannon, Beard, & Britt, ; O'Bannon, Britt, & Beard, ; Omar, Embi, & Yunus, ; Öztürk, ; Rachtam, Kaewkitipong, & Firpo, ; Rubrico & Hashim, ; Shih, ; Shraim, ; Souleles, ; Staines & Lauchs, ; Stankov, Glavinić, & Krpan, ; Varol, ; Vincent & Weber, ; Wang, Leng, & Lee, ).…”
Section: Formal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 98%
“…More than one‐third of the studies ( N = 26; 37.7%) leveraged on the opportunity to mix instructional content with information and resources, generated in outside settings and disseminated through different platforms (Akbari et al, ; Albayrak & Yildirim, ; Alias et al, ; Dogoriti et al, ; Geyer, ; Hurt et al, ; Karal et al, ; Kent, ; Lin et al, ; Miller, ; Omar et al, ; Öztürk, ; Parmaxi & Zaphiris, ; Penman & Thalluri, ; Prichard, ; Rachtam et al, ; Rambe, , , ; Shraim, ; Singh, ; Wang et al, ; Wang et al, ; Wang & Vasquez, ; Yen et al, ; Yunus et al, ).…”
Section: Formal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 99%
“…Within an educational context, Facebook has often been used as a supplementary instructional tool to lectures or LMSs to support class discussions or develop, deliver, and share academic content and resources. Many instructors have opted to create private Facebook groups, offering an added layer of security and privacy because groups are not accessible to strangers (Bahati, 2015;Bowman & Akcaoglu, 2014;Clements, 2015;Dougherty & Andercheck, 2014;Esteves, 2012;Shraim, 2014;Maben et al, 2014;Manca & Ranieri, 2013;Naghdipour & Eldridge, 2016;Rambe, 2012). The majority of studies on Facebook address behavioral indicators of student engagement, with far fewer focusing on emotional or cognitive engagement.…”
Section: Facebookmentioning
confidence: 99%
“…Researchers found that preference for Facebook over the university's LMS is due to perceptions that the LMS is outdated and unorganized and reports that Facebook is more familiar, convenient, and accessible given that many students already visit the social networking site multiple times per day (Clements, 2015;Dougherty & Andercheck, 2014;Hurt et al, 2012;Kent, 2013). In addition, students report that Facebook helps them stay engaged in learning through collaboration and interaction with both peers and instructors (Bahati, 2015;Shraim, 2014), which is evident in Facebook posts where students collaborated to study for exams, consulted on technical and theoretical problem solving, discussed course content, exchanged learning resources, and expressed opinions as well as academic successes and challenges (Bowman & Akcaoglu, 2014;Dougherty & Andercheck, 2014;Esteves, 2012Ivala & Gachago, 2012Maben et al, 2014;Rambe, 2012;van Beynen & Swenson, 2016).…”
Section: Facebookmentioning
confidence: 99%
“… Facebook enables various types of collaboration in a conducive environment and also allows teachers to trace the progress of the contributions by group members (Wong et .al, 2012) In addition to the reasons above some research results indicate that Facebook's strengths as a collaborative learning tool, among others: Facebook promotes collaborative work (Laura A Wankel and Patrick Blessinger, 2011), supports active learning (Junco, 2014), involves students in learning (Couillard in Patrut and Bogdan, 2013), encourages group collaboration. Roodt, Villiers, and Joubert (2012), drives positive attitudes of students to study (Shraim, 2014), facilitates multitasking (Lee, 2015), enhances flexibility (Ventura and Quero, 2013), and increase the familiarity and intensity of communication between educators and students and save costs (Hurt, et al,2012) The results of this study indicate that the use of Facebook in an online collaborative learning model is effectively used as a medium in learning. Besides having Facebook, it has various features that can function as a media that supports collaboration.…”
Section: Finding and Discussionmentioning
confidence: 84%